2010
DOI: 10.1007/s00044-010-9491-2
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, and urease inhibition of 5-substituted-8-methyl-2H-pyrido[1,2-a]pyrimidine-2,4(3H)-diones

Abstract: 5-Substituted-8-methyl-2H-pyrido[1,2-a]pyrimidine-2,4(3H)-dione and its anilines, amino pyridines and hydrazides derivatives were prepared in a good to excellent yields. In the first step 8-methyl-2H-pyrido[1,2-a]pyrimidine-2,4(3H)-dione (1) was prepared by reacting 4-methyl-2-aminopyridine, with diethylmalonate. Compounds substituted pyrido[1,2-a]pyrimidine-2,4(3H)-diones (PPMDO) (2)-(17) were prepared by condensing 8-methyl-2H-pyrido[1,2-a] pyrimidine-2,4(3H)-dione in the presence of triethylorthoformte (TEF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 33 publications
2
8
0
Order By: Relevance
“…Among the 21 synthesized compounds, five of them exhibited moderate to excellent urease inhibition. All these active compounds compromises of barbituric acid, N,N-dimethyl barbituric acid and thiobarbituric acid moiety and these are already known for their potency for urease inhibition [12][13][14][15]. Compound 16 exhibited ~91% inhibition and IC50 value of 17 μg/mL which in comparison to standard thiourea is more potent, similarly, compound 19 exhibited 82% inhibition and IC50 value of 36μg/mL.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the 21 synthesized compounds, five of them exhibited moderate to excellent urease inhibition. All these active compounds compromises of barbituric acid, N,N-dimethyl barbituric acid and thiobarbituric acid moiety and these are already known for their potency for urease inhibition [12][13][14][15]. Compound 16 exhibited ~91% inhibition and IC50 value of 17 μg/mL which in comparison to standard thiourea is more potent, similarly, compound 19 exhibited 82% inhibition and IC50 value of 36μg/mL.…”
Section: Resultsmentioning
confidence: 99%
“…Urease inhibition of newly synthesized compounds was determined by the modified phenol-hypochlorite method [10][11][12][13][14][15] (Table 1). Urease inhibition curve of thiourea was used as reference at varying concentrations i.e., 100, 10, 1, 0.1 and 0.01 µM.…”
Section: Urease Inhibition Assaymentioning
confidence: 99%
“…Recently, Rauf et al 69 demonstrated the synthesis of 5‐substituted‐8‐methyl‐2 H ‐pyrido[1,2‐ a ]pyrimidine‐2,4(3 H )‐dione and its derivatives for the evaluation of urease inhibition potential in concentration range from 100 to 0.01 µM. Among the synthesized compounds in this series, compound 32 was found to be the most potent at the 100 µM concentration exhibiting comparable urease inhibitory potential to thiourea, a standard urease inhibitor.…”
Section: Classes Of Urease Inhibitorsmentioning
confidence: 99%
“…Recently, the fused heterocyclic system functionalized imidazo[1,2‐a]pyridine has been recognized as an important pharmacophore, some of them were investigated as lipophilic parameter (log P) on the anti‐parasitic activity, docking simulations and anti‐inflammatory activity evaluation, of 2‐(N‐alkyl)amino‐3‐nitroimidazo[1,2‐a]pyridines, antiproliferative activity against melanoma cells, protein kinase inhibitors, antimicrobial activity and synergistic effects of novel organoselenium based imidazo[1,2‐a]pyridine compounds . The potential antipsychotic activity of fluorinated imidazo[1,2‐a]pyridine derivatives were also recognized as colon cancer cell lines HT‐29, and Caco‐2, antimicrobial screening, urease inhibition of 5‐substituted‐8‐methyl‐2H‐pyrido[1,2‐a]pyrimidine‐2, 4(3H)‐diones, and anticonvulsant studies of 6‐bromoimidazo[1,2‐a]pyridine‐2‐carbohydrazide derivatives …”
Section: Introductionmentioning
confidence: 99%